2022
DOI: 10.1515/chem-2022-0181
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of biomarkers and evaluation of antioxidant, anti-inflammatory, and cytotoxicity properties of Dodonaea viscosa grown in Saudi Arabia using HPTLC technique

Abstract: Dodonaea viscosa (Sapindaceae) was collected from Riyadh, Saudi Arabia. For the simultaneous measurement of quercetin and kaempferol, a validated high-performance thin-layer chromatography (HPTLC) approach was devised in D. viscosa leaf extract. The antioxidant activity was evaluated using diphenyl 1-picrylhydrazyl (DPPH) and 2,2′-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS) assays. Moreover, the cytotoxic effect was tested against three cancer cell lines A549, HepG2, and MDA-MB-231. The potential a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Therefore, preventing ROS-induced oxidative stress, lowering ROS levels, or both are used as a therapeutic strategy to protect brain tissue against the harmful effects of ROS in post-cerebral ischaemia. A previous study reported the scavenging activity of D. viscosa against DPPH radicals ( Almarfadi et al, 2022 ). In the present study, DVME protected against oxidative stress associated with transient brain ischaemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, preventing ROS-induced oxidative stress, lowering ROS levels, or both are used as a therapeutic strategy to protect brain tissue against the harmful effects of ROS in post-cerebral ischaemia. A previous study reported the scavenging activity of D. viscosa against DPPH radicals ( Almarfadi et al, 2022 ). In the present study, DVME protected against oxidative stress associated with transient brain ischaemia.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, oxidative stress plays a significant role in ischemic stroke, Consequently, antioxidant drugs have the potential to alleviate oxidative stress in the brain induced by ischemia ( Jelinek et al, 2021 ). In our previous study, we observed a substantial antioxidant activity in D. viscosa when compared to ascorbic acid using DPPH and ABTS scavenging assays ( Almarfadi et al, 2022 ). Building on this observation, we have formulated our hypothesis: administering a methanolic extract of D. viscosa may effectively counteract MCAO-induced oxidative stress, providing neuroprotection against ischemia–reperfusion injury in a rat model.…”
Section: Introductionmentioning
confidence: 95%
“…Since the majority of these methods have drawbacks, adverse effects, or both, tailored therapies that target RA's pathways are far more appropriate. Small molecule inhibitors are currently the subject of extensive research for a wide range of diseases and are thought to be one of the most effective forms of targeted therapy ( Almarfadi et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%